ANALISIS PENENTUAN HARGA POKOK PRODUKSI PADA KAIN TENUN SONGKET KHAS DESA BERATAN SAMAYAJI SEBAGAI ACUAN DALAM PENENTUAN HARGA JUAL (STUDI PADA PENGRAJIN KAIN TENUN DI DESA BERATAN SAMAYAJI): (Studi pada Pengrajin Kain Tenun di Desa Beratan Samayaji) - Made Saka Arya Wedanta; Putu Eka Dianita Marvilianti Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to analyze how the company calculates the cost of production as a reference in determining the selling price of songket woven fabrics on songket woven fabric craftsmen in Beratan Samayaji Village. This research was carried out in the Poetri Collection business, a business selling songket woven fabrics located in Beratan Samayaji Village, Buleleng District, Buleleng Regency. The type of data analysis used is qualitative dataThe results obtained regarding the calculation of the cost of production of songket woven fabrics are: (1) based on the calculation of craftsman A, it is worth Rp. 3,125,000/product, (2) based on the calculation of craftsman B, the value is Rp. 3,095,000/product, (3) based on the calculation using the full costing method, the cost of production for craftsman A is Rp. 3,225,000, (4) based on the calculation using the full costing method, the cost of production for craftsman B is Rp. 3,215,000/product. As for the selling price of cloth products, the calculation of accounting rules (mark up) is: (1) the selling price of craftsman A's cloth is Rp. 3,665,800/product, (2) the selling price of cloth to craftsman B is Rp. 3,641,000/product, (3) the selling price of cloth according to UD Poetri Collection is Rp. 4.460.00/product.